Prevalence of Dental Caries, Oral Hygiene Status, and Associated Risk Factors Among Schoolgoing Children of Rajshahi District in Bangladesh - Asad, Abul Kalam Mohammad; Barman, Ranjan Kumar; Huq, Md Munimul; Ali, Mir Nowazesh; Wahed, Mir Imam Ibne (TAJ: Journal of Teachers Association, 2022)
Introduction: Dental caries is one of the most prevalent and chronic oral diseases, particularly in childhood, associated with multifactorial causation. Objective: The study aimed to determine the prevalence of dental caries, oral hygiene status, and associated risk factors among school-going children of Rajshahi District in Bangladesh. Methods: This cross-sectional design type of descriptive study was carried out among primary school-going children of 5-13 years of age in the Rajshahi district. The sample size was 2000, and that was selected purposively. Data were collected through a partially structured questionnaire. Descriptive variables were explained with mean and standard deviation. The Chi-square test was applied to see the relationship with qualitative variables. Statistical significance was found by applying relevant statistical tests at an appropriate probability level (p<0.05 or <0.01). Results: A total of 2000 children between 5-13 years of age participated in this survey. The study findings showed a high prevalence of dental caries among 8–10-years old school children. Most (56.9%) of the respondents' fathers were workers, and most (86.3%) of the respondents' mothers were homemakers. It was found that 64.2% of the respondents' fathers and 74.05% of the respondents' mothers had below SSC level of education. About 60% of the respondents brushed their teeth twice a day, and a good number (81.0%) brushed their teeth before breakfast. The majority (68.80%) of the respondents had a family history of dental problems, and 45.6% had average oral hygiene. A large number (49.6%) of the respondents' favorite food was junk food. The relationship of age of the respondents with oral hygiene status was found to be statistically significant (p <0.001) but not with sex, parents' education, and occupation (p >0.05 each). The relationship of oral hygiene status of the respondents was found to be statistically significant with the frequency of tooth brushing (p <0.05), time of tooth brushing (p <0.01), family history of dental problems (p <0.05), most favorite food (p <.001), dental plaque index (p <0.001) and dental caries index (p <0.001). Conclusions: The prevalence of dental caries was higher among school-going children in the Rajshahi district of Bangladesh. TAJ 2022; 35: No-1: 125-136